Recent Advances in C-F Bond Cleavage Enabled by Visible Light Photoredox Catalysis - Lei Zhou (MDPI AG, 2021)
The creation of new bonds via C-F bond cleavage of readily available per- or oligofluorinated compounds has received growing interest. Using such a strategy, a myriad of valuable partially fluorinated products can be prepared, which otherwise are difficult to make by the conventional C-F bond formation methods. Visible light photoredox catalysis has been proven as an important and powerful tool for defluorinative reactions due to its mild, easy to handle, and environmentally benign characteristics. Compared to the classical C-F activation that proceeds via two-electron processes, radicals are the key intermediates using visible light photoredox catalysis, providing new modes for the cleavage of C-F bonds. In this review, a summary of the visible light-promoted C-F bond cleavage since 2018 was presented. The contents were classified by the fluorosubstrates, including polyfluorinated arenes, gem-difluoroalkenes, trifluoromethyl arenes, and trifluoromethyl alkenes. An emphasis is placed on the discussion of the mechanisms and limitations of these reactions. Finally, my personal perspective on the future development of this rapidly emerging field was provided.